2004
DOI: 10.1021/ie034303o
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Processing in High-Pressure Aqueous Environments. 7. Process Development for Catalytic Gasification of Wet Biomass Feedstocks

Abstract: Through the use of a metal catalyst, gasification of wet biomass can be accomplished with high levels of carbon conversion to gas at relatively low temperature (350 °C). In a pressurized-water environment (20 MPa), near-total conversion of the organic structure of biomass to gases has been achieved in the presence of a ruthenium metal catalyst. The process is essentially steam reforming, as there is no added oxidizer or reagent other than water. In addition, the gas produced is a medium heating value gas due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…If coke is formed on the surface of the catalysts, the high H 2 O concentration helps in keeping it clean via gasification. In accordance with that it was found that coke formation on the catalyst surface is a minor problem [8].…”
Section: Catalytic Gasification In Hot Compressed Watersupporting
confidence: 75%
See 3 more Smart Citations
“…If coke is formed on the surface of the catalysts, the high H 2 O concentration helps in keeping it clean via gasification. In accordance with that it was found that coke formation on the catalyst surface is a minor problem [8].…”
Section: Catalytic Gasification In Hot Compressed Watersupporting
confidence: 75%
“…The difference with respect to the product between 350 and 600 8C is its composition: at low temperature the gas contains nearly only CH 4 and CO 2 (see ref. [8] and Fig. 5B) whereas at higher temperature it is a mixture of CH 4 , H 2 and CO 2 .…”
Section: Experimental Results Of Model Components Gasification In Hotmentioning
confidence: 91%
See 2 more Smart Citations
“…Sulfur also exists in some waste biomass and it has an influence on supercritical water gasification. Elliott et al claimed that the presence of sulfur lowered the activities of ruthenium catalysts in subcritical water at 623 K (Elliott et al, 2004). Osada et al studied the effect of sulfur on SCWG of lignin at 673K with the catalysis of supported ruthenium (Osada et al, 2007a).…”
Section: (C) Influence Of Inorganic Elementsmentioning
confidence: 99%